Perception and correlates of excessive vaginal discharge in rural women - Mammen, Sheena A.; Singh, Shavinder; Rajesh, Isaac; Goyal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vaginal discharge is one of the most common symptoms of gynecological morbidity. Vaginitis is the most prevalent cause. Gynecological disorders have substantial impact on female health and behaviour. Recent evidence suggests that the association between the complaint of vaginal discharge and the presence of Reproductive Tract Infections is weak. Women who are overanxious, introspective or suffering from fears of venereal disease and cancer tend to exaggerate the complaint of vaginal discharge into something pathological. The objective of the study was to study rural women’s perception and health care seeking behaviour regarding excessive vaginal discharge. To study various psychological and biological correlates of excessive vaginal discharge Methods: This was a community based cross sectional study, conducted in the rural field practice areas under the Department of Community Medicine, Christian Medical College, Ludhiana. House to house surveys were conducted with semi-structured questionnaire and GAD 7 (Generalised Anxiety Disorder) scale, using systematic random sampling. Results: 160 rural women were interviewed to collect data. Of them, 27.5% reported having excessive vaginal discharge. There was no association observed between menstrual hygiene methods and excessive vaginal discharge (p= 0.77). Association couldn’t be observed with selection of barrier and other non-barrier methods of contraception (p= 0.09) either. Statistically significant association was observed between presence of anxiety and vaginal discharge (p=0.01). Conclusions: All vaginal discharges are not pathological. Causative factor of excessive vaginal discharge may not be infections always. There was a statistically significant association between anxiety and perceived vaginal discharge.